eHealth literacy among hospital health care providers: a systematic review - Gunhild Brørs; Marie Hamilton Larsen; Linn Benjaminsen Hølvold; Astrid K. Wahl (BMC, 2023)
Abstract Background eHealth literacy is a key concept in the implementation of eHealth resources. However, most eHealth literacy definitions and frameworks are designed from the perceptive of the individual receiving eHealth care, which do not include health care providers' eHealth literacy or acceptance of delivering eHealth resources. Aims To identify existing research on eHealth literacy domains and measurements and identify eHealth literacy scores and associated factors among hospital health care providers. Methods This systematic review was reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 checklist. A systematic literature search was conducted in MEDLINE, Cinahl, Embase, Scopus, PEDro, AMED and Web of Science. Quantitative studies assessing eHealth literacy with original research, targeting hospital health care providers were included. Three eHealth literacy domains based on the eHealth literacy framework were defined a priori; (1) Individual eHealth literacy, (2) Interaction with the eHealth system, and (3) Access to the system. Pairs of authors independently assessed eligibility, appraised methodological quality and extracted data. Results Fourteen publications, of which twelve publications were conducted in non-Western countries, were included. In total, 3,666 health care providers within eleven different professions were included, with nurses being the largest group. Nine of the included studies used the eHealth literacy scale (eHEALS) to measure eHealth literacy, representing the domain of individual eHealth literacy. A minority of the studies covered domains such as interaction with the eHealth system and access to the system. The mean eHEALS score in the studies ranged from 27.8 to 31.7 (8-40), indicating a higher eHealth literacy. One study reported desirable eHealth literacy based on the Digital Health Literacy Instrument. Another study reported a relatively high score on the Staff eHealth literacy questionnaire. eHealth literacy was associated with socio-demographic factors, experience of technology, health behaviour and work-related factors. Conclusions Health care providers have good individual eHealth literacy. However, more research is needed on the eHealth literacy domains dependent on interaction with the eHealth system and access to the system. Furthermore, most studies were conducted in Eastern and Central-Africa, and more research is thus needed in a Western context. Trial registration PROSPERO International Prospective Register of Systematic Reviews (CRD42022363039).